« Clio en scène », ou le théâtre d’histoire immédiate au prisme des Humanités numériques - Virginie Yvernault; Élisabeth Angel-Perez; Line Cottegnies (Sillages Critiques)
This note recalls the aims of the project entitled « Clio on Stage : Making History – Immediate History on the British Stage », based at Sorbonne Université between 2019 and 2021. The project proceeds from the remark that both early modern theatre and contemporary theatre tend to show a predilection for objects that have to do with recent or immediate history. The article traces the successive steps which have led to the creation of a relational database which includes a corpus of over a hundred plays (mostly British, but with also a few French ones), and offers a non-exhaustive analysis of the first results provided by the database.